(untitled) (Scientific journal of the Fergana State University, 2025)
The article investigates the methods and means of constructing artistic truth on the basis of life reality and historical truth. It specifically emphasizes how creative material is accumulated through visual, auditory, tactile, gustatory, and olfactory perceptions within the context of life experience, and the role of the author’s concept in transforming this material into artistic interpretation. Furthermore, the study clarifies the function of historical works, literary-historical sources, architectural monuments, regional-geographical observations, archival documents, contemporary memoirs and interviews, as well as cultural realia as sources of historical truth within the structure of a literary work.